Sex, Love and Marriage, by Paul Flaman - Sevjarynec, Hanna Kanstancinaŭna (Religious studies and theology, 2016)
Sex, Love and Marriage, by Paul Flaman. Ottawa, Justin Press, 2015. 300pp., Pb. $23.95. ISBN-13: 9780991934294.